What’s Happening with Internet Use in Alberta Schools? - Oberg, Dianne; Gibson, Susan (Alberta Journal of Educational Research, 1999)
Data on Internet use in public and separate schools in Alberta were gathered from principals and teachers using a Likert-scale questionnaire and chi-square testing for significance. Respondents were motivated to learn to use the Internet primarily by personal interest, and trial and error was the most frequently reported approach to learning about the Internet. Principals were more positive than teachers about the adequacy of school and district support for Internet use. Principals used the Internet mostly for e-mailing colleagues and for accessing district and ministry information, whereas teachers used it mostly for finding instructional materials. Fewer than 40% of the teachers engaged their students in Internet use for more than one hour a week. The respondents were evenly divided between experienced and novice users. Users differed mainly on the nature and amount of their Internet use.